Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 3 - Differentiation - 3.3 Product and Quotient Rules - Exercises - Page 122: 41



Work Step by Step

$G(x)=(g(x))^{2}=g(x)\cdot g(x)$ Applying the product rule, we get $G'(x)=g'(x)\cdot g(x)+g(x)\cdot g'(x)=2(g(x)\cdot g'(x))$ $G'(4)=2(g(4)\cdot g'(4))=2(5\times-1)=-10$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.